Public support for carrot, stick, and no-government water quality policies. Issue 76 (October 2017) - Rissman, Adena R.; Kohl, Patrice A.; Wardropper, Chloe B.
Highlights: This study examines farm and lawn water policy support among residents in southern Wisconsin, USA. Residents supported carrot and stick water quality policies, but opposed relying on voluntary action without government. Cultural worldview strongly predicted policy support, followed by runoff concern, water quality perception, self-interest. Stick approaches were polarizing, with less support among individualists and greater support among communitarians. Self-interest helps explain opposition to sticks for oneself but support for sticks for other pollution sources. Abstract: Public support for environmental policy provides an important foundation for democratic governance. Numerous policy innovations may improve nonpoint source pollution, but little research has examined which types of individuals are likely to support various runoff reduction policies. We conducted a household mail survey of 1136 residents in southern Wisconsin. In general, residents were more likely to support water quality policies if they were communitarians, egalitarians, concerned about water pollution, and perceived water quality as poor. The majority of respondents somewhat to strongly supported all of the seven proposed water quality policies, but opposed relying on voluntary action without government involvement on farms. Residents had higher support for incentives and market-based approaches (carrot policies) than regulation and taxes (stick policies). A more complicated pattern emerged in within-subject comparisons of residents' views of carrot and stick approaches. Stick approaches polarized respondents by decreasing support among people with individualistic worldviews, while slightly increasing support among people with communitarian worldviews. Residents with an agricultural occupation were more likely to support voluntary, non-governmental approaches for reducing agricultural runoff, and were also more likely to support regulation for reducing urban lawn runoff. This research highlights the dominant role of cultural worldviews and the secondary roles of water pollution concern, perceived water quality, and self-interest in explaining support for diverse policies to reduce nonpoint source pollution.